Aromatherapy Management to Reduce Stress - Puput Mulyono; Singgih Purnomo (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Background: Stress is a major health threat. According to the 2022 adolescent mental health survey, 15.5 million (34.9 percent) adolescents experience mental problems and 2.45 million (5.5 percent) adolescents experience mental disorders. The results of a survey at the University of Indonesia showed that 50% of students who were doing their thesis experienced stress. This can be overcome with non-pharmacological therapy using peppermint incense aromatherapy to reduce stress levels when preparing a thesis for